2007
DOI: 10.1055/s-2006-945005
|View full text |Cite
|
Sign up to set email alerts
|

Neuritenwachstum in vitro durch BDNF und GDNF in Kombination mit Dexamethason auf kultivierte Spiralganglienzellen

Abstract: Neurite outgrowth induced by neurotrophic factors could not be observed to be reduced when dexamethasone is given at the same time. Therefore the demonstrated results provide a basis for further animal studies in this field of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These observations are akin to those of others in SGNs (Stöver et al, 2007; Wefstaedt et al, 2005; Wei et al, 2007) and other neuronal cell types (Ledda et al, 2002; Paratcha et al, 2001); e.g. Wefstaedt et al (2005) found that 100 ng/ml of GDNF increased the number of neurite-bearing SGNs in dissociated neuron cultures.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These observations are akin to those of others in SGNs (Stöver et al, 2007; Wefstaedt et al, 2005; Wei et al, 2007) and other neuronal cell types (Ledda et al, 2002; Paratcha et al, 2001); e.g. Wefstaedt et al (2005) found that 100 ng/ml of GDNF increased the number of neurite-bearing SGNs in dissociated neuron cultures.…”
Section: Discussionsupporting
confidence: 80%
“…However, early postnatal SGNs were not used in this study and a dose of GDNF (100 pg/ml) was used, being substantially lower than doses that were effective in our hands as well as those of several investigators using other systems (e.g. Hauck et al, 2006; Uchida et al, 2006; Villegas et al, 2006), including SGs of different species (Maruyama et al, 2007; Stöver et al, 2007). Numbers of cell bodies per explant could not be discerned in our explants, being too bulky for visualization of individual structures within.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study confirmed that cell-derived human BDNF has a neuroprotective effect on SGN. Several other studies showed an enhanced SGN survival in vitro [13,37,40,45] and in vivo [15,46,47], which was mediated by BDNF. However, an analogous neuritogenesis as determined by measuring the neurite length of SGN was not observed in the herein presented study.…”
Section: Discussionmentioning
confidence: 97%